PENINGKATAN KUALITASGURU SMU MELALUI PROGRAM PGSMU - Das Salirawati, Das Salirawati (Jurnal Cakrawala Pendidikan, 2016)
The teaches have an itnportant role 0 determine the quality of education general and of teaching learning in particular. As hUlnan Ressources ini the aduc.ation sector, the teachers are demanded 0 develop ang to increse their quaity that related to their teaching -quality as well as their knowladge quality. This is relevant to their profesion that have to follow the era development. Senior Secondary School Teacher Education (SSSTE) has been issued’ by governlnent through the Government Regulation No. 30, 1990 However, many participants of the SSSTE however program just appear in the academic year 1999/2000 indicated by the fact that many SMU teachers undertake this program in certain universttles such as the State University ofYogyakarta. This progranl is organized with the aim ti j’hcrease the quality of SMlJ teachers who have tacher’s cetificate of D3 to become S I Degree. It is expected that the improvement the teacher’s quality as HUlnan Resources in the education sector can be achieved through the SSSTE prograln; The study ternl of SSSTE f01’ about 10 1110unths is enough to give. the enrichlnent Inaterial and to broaden the concept of the students. Novertheless the success of the SSSTE progranl to inlprove teacher’s quality of SMU depands on the teaacher own efforts in study. Teachers motivation and awareness about their responsibility ii improve education quality in Indonesia is the key ofsuccess ofthe sssrrE prograln